Pengangguran, Lama Mencari Kerja, dan Reservation Wage Tenaga Kerja Terdidik - Pasay, N. Haidy. A.; Indrayanti, Ratna (UI Scholars Hub, 2012)
Number of educated unemployment is increasing every year. Of the 8.59 million unemployed labor force in 2010, 4.8 million of whom are middle and high educated unemployed. Meanwhile, unemployment duration was 11 months. Two step Heckman method is employed to estimate reservation wage. The OLS estimates duration of search for educated unemployment as well as by social, demographic, and regional characteristics. Search duration for middle and high educated workforce is longer than low educated workforce. The reservation wage of highly educated labor force by social, demographic, and regional characteristics is higher than other labor force.